1997
DOI: 10.1074/jbc.272.46.28980
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Norvaline at Leucine Positions in Recombinant Human Hemoglobin Expressed in Escherichia coli

Abstract: We report here a novel finding that norvaline can be incorporated in place of leucine in recombinant human hemoglobin expressed in Escherichia coli. The presence of the norvaline was confirmed by several analytical methods such as amino acid analysis, peptide mapping, electrospray mass spectrometry, and Edman protein sequencing. It appears that substitution is distributed across both the ␤-and di-␣-globins in purified recombinant hemoglobin. The level of misincorporation correlated with the ratio of the free n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
100
1
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(111 citation statements)
references
References 26 publications
7
100
1
2
Order By: Relevance
“…Second, Asn starvation studies have also shown (24,25) that the frequency of misreading of the Asn codon, AAU, is much higher (2-10-fold) than for the AAC codon, whereas we see no codon preference even though about two-thirds of the Asn codons in our proteins are AAU. Third, mischarging, as seen here, is not codon-related but results from the attachment of a different but structurally related amino acid to its cognate tRNA; misincorporation can be prevented by supplementing the culture medium with the cognate amino acid, Asn, in this case (11,26).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, Asn starvation studies have also shown (24,25) that the frequency of misreading of the Asn codon, AAU, is much higher (2-10-fold) than for the AAC codon, whereas we see no codon preference even though about two-thirds of the Asn codons in our proteins are AAU. Third, mischarging, as seen here, is not codon-related but results from the attachment of a different but structurally related amino acid to its cognate tRNA; misincorporation can be prevented by supplementing the culture medium with the cognate amino acid, Asn, in this case (11,26).…”
Section: Discussionmentioning
confidence: 99%
“…However, when Asn is not present in sufficient amounts, other amino acids, especially ones with the most similar structures and physical and chemical properties, will be misactivated so that biosynthesis can continue. The misincorporation of norvaline, a non-protein amino acid, at leucine positions in recombinant human hemoglobin when the ratio of norvaline to leucine in culture medium is high is a good example (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…E. coli (Ec) LeuRS activates several noncognate amino acids in vitro, including isoleucine, valine, methionine, and norvaline (Nva) (21, 30 -33). Among these, norvaline is a nonproteinogenic amino acid that is of particular importance because it can be incorporated into recombinant proteins in place of leucine (34). It was recently demonstrated that the in vivo concentration of norvaline in the cell may rise to 1 mM under anaerobic growth conditions (35).…”
mentioning
confidence: 99%
“…Leucyl-tRNA synthetase (LeuRS) and two other closely related aaRSs [isoleucyl-(IleRS) and valyl-(ValRS) tRNA synthetases] that aminoacylate aliphatic amino acids have been well documented to misactivate and edit noncognate amino acids that structurally overlap with their respective substrates (10)(11)(12)(13)(14)(15)(16)(17)(18)(19). The hydrolytic editing active site for each of these enzymes is located within homologous domains called the connective polypeptide 1 [CP1 (13,14,16,(19)(20)(21)(22)(23)(24)(25)(26)].…”
mentioning
confidence: 99%